Importance of cash flow optimization of enterprises - Rohanova, Hanna (My University, 2018)
The necessity of cash flows steady monitoring proved and importance of their optimization determined. Factors influencing onto the cash flows volume and character of their forming in time determined.
Keywords: cash flow; optimization; solvency; грошовий потік; оптимізація; платоспроможність; фінанси; кафедра фінансів